'As many options as there are, there are just not enough for me': Contraceptive use and barriers to access among Australian women. (October 2014) - Dixon, Suzanne C.; Herbert, Danielle L.; Loxton, Deborah; Lucke, Jayne C.
Abstract Objective A comprehensive life course perspective of women's experiences in obtaining and using contraception in Australia is lacking. This paper explores free-text comments about contraception provided by women born between 1973 and 1978 who participated in the Australian Longitudinal Study on Women's Health (ALSWH). Methods The ALSWH is a national population-based cohort study involving over 40, 000 women from three age groups, who are surveyed every three years. An initial search identified 1600 comments from 690 women across five surveys from 1996 (when they were aged 18–23 years) to 2009 (31–36 years). The analysis included 305 comments from 289 participants. Factors relating to experiences of barriers to access and optimal contraceptive use were identified and explored using thematic analysis. Results Five themes recurred across the five surveys as women aged: (i) side effects affecting physical and mental health; (ii) lack of information about contraception; (iii) negative experiences with health services; (iv) contraceptive failure; and (v) difficulty with accessing contraception. Conclusion Side effects of hormonal contraception and concerns about contraceptive failure influence women's mental and physical health. Many barriers to effective contraception persist throughout women's reproductive lives. Further research is needed into reducing barriers and minimising negative experiences, to ensure optimal contraceptive access for Australian women.